Analysis Of Organic Waste Management In Padang Baru Lubuk Basung Traditional Market - rahayu, rahayu; miftahurahmah, miftahurahmah (Institut Agama Islam Sumatera Barat, 2023)
Based on observations organic waste at the Padang Baru Traditional Market Lubuk Basung is scattered everywhere, when selling traders do not provide temporary trash bins and later after being cleaned by market officials the waste is immediately thrown into the trash, the waste is just piled up in one tub and left unattended. Processed so as to cause a foul odor that can disturb the surrounding community or can cause various diseases and environmental pollution. Organic waste in the Lubuk Basung Padang Baru Traditional Market has good potential if managed properly. The purpose of this study was to analyze the management of organic waste at the Lubuk Basung Padang Baru Traditional Market. The research method is a qualitative method. The place of this research is in Lubuk Basung Padang Baru Traditional Market. The respondents that the researchers took were seven people, namely four market traders, two local people and one market manager. The research instruments are observation, interviews and documentation. The author uses data analysis in three ways: data reduction, data presentation, and drawing conclusions. The research findings obtained by the author are that organic waste in the Lubuk Basung Padang Baru Traditional Market is not managed properly by market traders, market leaders and the surrounding community. There is no waste segregation and composting. From this it can be concluded that the results of the author’s analysis entitled “Analysis of Organic Waste Management in Lubuk Basung Padang Baru Traditional Market” are not managed properly.